Traveling; advertise tourism destinations while relieve stress - Sakti, Intan Widuri; Mariana, R. Adjeng (CENTRAL ASIA AND THE CAUCASUS, 2022)
Traveling is one way to release stress from the hustle and bustle that occurs in our daily activities. With many things that we get from traveling experiences, we often document or keep them as mementos in various ways, for example the photos we post on social media, whatsapp status updates even with tempting captions so that they want to travel too for those who see them. The things that have been done without realizing it have carried out indirect promotions, namely providing information about what tourist attractions are, the variety of food, the beauty of tourist destinations, the shortcomings and advantages, and this is often expressed in the form of testimonials. With so many events like this, promotion of tourist destinations can be said to happen automatically. This is reduced to the element of motivation to travel to the emergence of travel decision-making.